Risk Analysis of Work Accidents Using HIRADC and JSA to Achieve Zero Accident in the Electricity Industry - Ega Rizkiyah; Luh Putu Intan Saraswati (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2026)
Workplace accidents remain a serious problem across industrial sectors because they can lead to severe injuries, fatalities, and material losses. In Indonesia, workplace accident cases reached 356,383 as of October 2024, indicating the urgent need for more effective occupational safety risk control. This research identifies and analyzes occupational safety risks in the electricity industry, which is characterized by potential exposure to chemical, mechanical, ergonomic, and physical hazards. This research integrates Hazard Identification, Risk Assessment, and Determining Control (HIRADC) with Job Safety Analysis (JSA). HIRADC was used to identify, classify, and assess hazard levels across eight work areas, while JSA was applied to examine the most critical activity identified from the risk assessment results. Based on observations, interviews, and company reports in 2024, 498 findings were identified, of which 59% were negative findings caused by unsafe actions and unsafe conditions. The risk recapitulation showed that 76% of potential hazards were classified as high risk, 22% as moderate risk, and 2% as low risk. Area 2 recorded the highest average risk score of 9.20, while Area 4 had the largest number of hazards, with 10 findings and a maximum risk score of 12. Mechanical hazards were the most frequently identified hazard type, accounting for 18 findings, or 42.9% of the total hazards, whereas physical hazards had the highest average risk score of 8.90. The JSA results indicated that generator maintenance was the most critical activity because it involved multiple hazard types, including electrical, mechanical, physical, and chemical hazards. The proposed control measures were formulated based on the hierarchy of controls, particularly administrative controls and personal protective equipment. These findings suggest that integrating HIRADC and JSA can support electricity companies in identifying critical hazards, prioritizing preventive actions, and strengthening occupational safety management toward zero accident performance.